Control and Modelling of PV –Wind Hybrid Energy Sources for Desalination System - Heba S. Abd-El Mageed; Hanaa M. Farghally; Faten H. Fahmy; Mohamed A. Abuo-Elmagd (Institute of Advanced Engineering and Science, 2015)
Hybrid renewable energy based on PV and wind systems complemented with battery storage system are starting to play a vital role over the world to supply power to distant regions. This paper proposes the combination of lead acid battery system with a typical hybrid PV-wind energy system for supplying the electrical load of a desalination system at Mersa Matrouh. Solar and wind are sources of energy and battery unit is considered as a storage unit to meet the load demand. Simulation model with MATLAB/Simulink for the hybrid power system has been developed considering power supply variation in solar and wind hybrid power system caused due to disturbed power supply from wind turbine generator and solar system. A control strategy using Neural Network Control (NNC) is being offered and analyzed. The final result of the simulation indicates an effective operation of battery. DOI: http://dx.doi.org/10.11591/telkomnika.v14i1.7650